2018
DOI: 10.1371/journal.pone.0201220
|View full text |Cite
|
Sign up to set email alerts
|

The anticancer peptide RT53 induces immunogenic cell death

Abstract: In recent years, immunogenic cell death (ICD) has emerged as a revolutionary concept in the development of novel anticancer therapies. This particular form of cell death is able, through the spatiotemporally defined emission of danger signals by the dying cell, to induce an effective antitumor immune response, allowing the immune system to recognize and eradicate malignant cells. To date, only a restricted number of chemotherapeutics can trigger ICD of cancer cells. We previously reported that a peptide, calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 58 publications
3
41
0
Order By: Relevance
“…Similar results were obtained with inhibition of caspase-1, caspase-3/7 and caspase-8 (Figure S3B). These results are in agreement with caspase-independent mechanism of cytotoxicity induced by RT53 in cancer cells (24).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were obtained with inhibition of caspase-1, caspase-3/7 and caspase-8 (Figure S3B). These results are in agreement with caspase-independent mechanism of cytotoxicity induced by RT53 in cancer cells (24).…”
Section: Resultssupporting
confidence: 90%
“…Although the mechanisms associated with its anti-apoptotic activity have not been clearly elucidated, AAC-11 contains several protein interaction domains, including a leucine zipper (LZ) domain (19), and has been proposed to repress apoptotic effectors such as E2F1 (20), Acinus (21) and caspase-2 (22). Synthetic peptides based on the LZ domain sequence of AAC-11 were previously shown to be cytotoxic to cancer cells both in vitro and in a in vivo mouse model of melanoma (23, 24) or acute leukemia (25).…”
Section: Introductionmentioning
confidence: 99%
“…There are few scientific reports on the use of synthetic peptides that can induce ICD 45‐47 . Herein, we assessed the ability of PKHB1, the first serum‐stable CD47‐agonist peptide: (i) to induce selective cell death in T‐ALL cells with conserved characteristics of CD47‐mediated cell death; and (ii) to determine whether this type of cell death is immunogenic.…”
Section: Discussionmentioning
confidence: 99%
“…There are few scientific reports on the use of synthetic peptides that can induce ICD. [45][46][47] Herein, we assessed the ability of PKHB1, the first serum-stable CD47-agonist peptide: (i) to induce selective cell death in T-ALL cells with conserved characteristics of CD47mediated cell death; and (ii) to determine whether this type of cell death is immunogenic. We observed that PKHB1 induced death in CEM, MOLT-4, and L5178Y-R cells (Figure 1), in a fast caspaseindependent process that implicates phosphatidylserine exposure along with plasma membrane permeabilization, and loss of mitochondrial membrane potential (Figure 2) that is selective for malignant cells (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In LXR agonist-treated Balb/c mice, CRT and HMGB1 expression levels were increased and the LXR agonists exhibited tumour vaccine effects by inducing ICD. 51 Similarly, the oncolytic peptides RT53 and LTX-315 also trigger the exposure of CRT and the release of HGMB1 and ATP as obligatory signals for ICD [48][49][50] ; however, concerning the induction mechanism, and triggering classic immunogenic cell death. Mitochondrial outer membrane permeabilization (MOMP) is another factor that stimulates NF-κB activity and subsequently induces caspase-independent cell death (CICD), which is also regarded as ICD…”
Section: Conclusion and Further Perspec Tivesmentioning
confidence: 99%